Critical Literacy Approach in the teaching of literary appreciation using Indonesian short stories - Halimah, H.; Sumiyadi, S.; Mulyati, Yeti; Damaianti, Vismaia S. (Indonesian Journal of Applied Linguistics, 2020)
This paper presents experimental results about the use of the Critical Literacy Approach (CLA) in literary appreciation using Indonesian short stories. The purpose of the study is to find better teaching strategies to improve students’ critical thinking skills and critical awareness to comprehend the conditions of the world, including social relationships involving disproportionate power relations. This study uses the randomized pretest-posttest control group design (RPPCGD), which is a randomized design by giving pretest and posttest to the experimental group (CLA) and control group (expository). The effect of both teaching strategies is calculated through the difference between the pretest and posttest of both groups. This research involved 170 students in the Department of Indonesian Language and Literature Education of an education university in Indonesia. The results are presented in the form of analytical descriptions of paired samples test and paired samples correlations of each group. The results show that students who did a short story analysis with CLA had significantly increased critical thinking skills and critical awareness compared to students of expository strategy. The average posttest of the experimental group is 80.33, which is considerably higher than the control group, with an average of 76.13. The average increase in skills (posttest-pretest) of the experimental group is 38.71 points, and the control groups have an average increase of 31.19 points. Therefore, it is clear that the teaching of literary appreciation using Indonesian short stories with CLA is effective. The use of CLA strategies in increasing students’ critical thinking skills and critical awareness through literary appreciation of Indonesian short stories shows positive results. The results of this study can contribute to the field of learning design with new ideas to improve critical thinking skills and critical awareness of Indonesian students through effective short story analysis or fictional prose analysis.